DESIGNÂ INOVASIÂ Â MEDIAÂ FLASHCARDÂ MAHASISWAÂ PGÂ PAUDÂ UMSURABAYAÂ UNTUKÂ MENANAMKANÂ KONSEPÂ Â MEMBILANGÂ ANGKAÂ 1Â â€“Â 9Â Â PADAÂ ANAKÂ USIAÂ DINIÂ - wahono wahono (Universitas Muhammadiyah Surabaya, 2016)
ThisÂ studyÂ aimsÂ toÂ inspireÂ teachersÂ (PAUD)Â andÂ toÂ gainÂ anÂ overviewÂ ofÂ theÂ use flashcardÂ mediaÂ InÂ EnhancingÂ TheÂ AbilityÂ ToÂ InstillÂ TheÂ ConceptÂ OfÂ CountingÂ NumbersÂ 1â€9 InÂ EarlyÂ Childhood.Â ResearchÂ wasÂ conductedÂ onÂ studentsÂ TheÂ studyÂ programÂ Teacher EducationÂ EarlyÂ ChildhoodÂ Education,Â UniversityÂ ofÂ MuhammadiyahÂ Surabaya.Â Experience teachesÂ countingÂ theÂ mostÂ widelyÂ experiencedÂ byÂ childrenÂ agedÂ fiveÂ andÂ sixÂ years. 90%Â of theÂ observationÂ ofÂ earlyÂ childhoodÂ teachersÂ teachÂ theÂ conceptÂ ofÂ countingÂ theÂ numbersÂ 1â€9Â areÂ correct.Â ToÂ strengthenÂ theÂ child'sÂ responses,Â teacherÂ invitesÂ childrenÂ toÂ countÂ the numberÂ ofÂ fingersÂ togetherÂ leftÂ handÂ andÂ rightÂ hand.Â AfterÂ theÂ childrenÂ wereÂ askedÂ toÂ try yourselfÂ countingÂ theÂ fingersÂ ofÂ theirÂ leftÂ andÂ rightÂ hands. FromÂ interviewsÂ withÂ teachersÂ andÂ parentsÂ 85%,Â theÂ They'veÂ beenÂ ableÂ toÂ train childrenÂ toÂ countÂ theÂ objectsÂ thatÂ existÂ aroundÂ childrenÂ whetherÂ atÂ home,Â onÂ theÂ road,Â as wellÂ asÂ schools.Â FromÂ theÂ observationsÂ gatheredÂ researchersÂ foundÂ 75%Â ofÂ teachersÂ and parentsÂ haveÂ not beenÂ usedÂ toÂ teachÂ countingÂ whileÂ bernyannyi,Â childrenÂ areÂ introducedÂ to theÂ conceptÂ ofÂ numbers,Â forÂ exampleÂ throughÂ theÂ songsÂ thatÂ matchÂ theÂ numbersÂ thatÂ will beÂ introduced,Â forÂ example:Â theÂ songÂ IÂ loveÂ mom. Â Keywords:Â flashcardÂ media,Â countÂ theÂ numbersÂ 1â€9